中国相亲角：中国式婚姻返传统的现象 —— "门当户对"及父母的介入 = China's matchmaking corner: the phenomenon of Chinese marriage reverting to traditional customs of matched marriages and parental involvement - 杨游游 Yeoh, You You (Nanyang Technological University, 2024)
中国式婚姻自古以来有着很严厉的规矩，尤其讲究“门当户对”和“父母之命，媒妁之言”。无可否认，20世纪的年轻人越多反对传统的由父母、媒人做主的婚姻，而倾向于恋爱、婚姻自由与自主，但在21世纪初，中国公园却出现了一个独特的现象——相亲角。在相亲角，由父母承担传统媒人的角色，成为帮忙子女相亲的核心人物。在这里，相亲犹如一场交易，父母把子女的社会经济条件和择偶标准直白地列在挂牌上，等待着一个符合条件的对象出现。父母择偶标准的苛刻与一致化反映了中国式婚姻的市场化与功利化，也侧面显示出了中国式婚姻返传统的现象。 本文将从“门当户对”的择偶标准和父母在年轻人婚事的介入来证明中国式婚姻重返传统的趋势，并且通过中国的政治历史与社会局势来探讨传统婚姻模式在相亲角重现的原因。关键词：相亲角、中国式婚姻、“门当户对” Chinese marriages have a history of strict procedures since ancient times, especially in the tradition of arranged marriage matched and approved by parents and matchmakers. Undeniably, the 21st century youths today favour the freedom and autonomy in relationships and marriage, generally discarding the traditional form of marriage dictated by parents and matchmakers. Yet, a unique phenomenon has emerged in China’s unsuspecting parks – Matchmaking Corners. In these Matchmaking Corners, the parents absorb the role of the matchmaker and become the sole and central figures for this traditional process. Matchmaking becomes transactional – they present their child’s socioeconomic conditions unabashedly on posters and papers while applying equally rigorous judgement on potential matches. The desired criteria are cruelly harsh in standards, reflecting the marketisation and utilitarianism of Chinese marriages, and also demonstrating the trend of Chinese marriages reverting to traditional mode. In this paper, I will look at the Chinese’ obstinate preoccupation with the idea of manifesting the “Right Match” and parental involvement in youth marriages, to demonstrate the reversion of Chinese marriages into its traditional marriage models. Contingent reasons for the resurgence of this traditional model of marriage will be analysed cognisant of China’s political history and present social conditions. Keywords: Matchmaking Corner, Chinese marriage, match marriage